Green port performance evaluation under uncertainty: a multiple attribute group decision analysis. (22nd January 2021) - Zhao, Dan; Bao, Tiantian; Cullinane, Kevin; Wang, Yuhong
This paper aims to assess the performance of a port within the context of its supply chain on the basis of integrating a five-dimensional balanced scorecard with green performance criteria. A multiple attribute group decision-making (MAGDM) approach is proposed which encompasses both intuitionistic fuzzy set theory and evidence theory in order to properly represent and aggregate the uncertain information which prevails within any process of such an evaluation. With an empirical application, the evaluation results provide effectively not only the ranking order of all alternative port enterprises, but also the strengths and weaknesses of each one, at the detailed level of individual performance attributes.